Estudo comparativo de diferentes campos eletromagnéticos na proliferação, viabilidade, quantificação de proteínas e diferenciação de osteoblastos - Souza, Ana Maria de (2016)
Phototherapy has been widely used in the treatment of osteo-degenerative diseases, with the objective of evaluating its effects on bone metabolism. Clinical observations have suggested that low intensity light therapy has beneficial effects on the bone healing process. Although specific clinical protocols have not yet been established, several authors have reported photobiomodulatory effects on healing processes in animal models and tissue culture media. Little is known about the effects of different spectra on the viability and differentiation of rat calvarial osteoblasts (ÓSTEO 1). Therefore, the objective of this work was to compare the influence of phototherapy with LBI, LED's and Magneto on the viability and differentiation of osteoblasts from calvaria of rats (ostreat 1). For this study the osteoblasts were cultured in 10% DMEM and 5% fetal bovine serum (FBS) culture and incubated in a CO2 oven. The cells were irradiated with 660 nm (red), 808 nm (infrared), 660 nm (red) LEDs, 850 nm (infrared) at 40 mW at 1.5 and 10 J / cm² . After cell adhesion, we used the magneto equipment with frequency of 0, 9 and 18 Hertz, at exposure times of 25, 125 and 250 seconds. 24 hours after irradiation, the viability analysis wasperformed by MTT and Violet Crystal assay in which the results suggest a partial increase of viable cells when stimulated by different spectra. For the cell differentiation assays, the activity of alkaline phosphatase was increased with Magneto at 9 hertz (250 seconds), Red Laser at 250 seconds and Infrared at 125 seconds in relation to the control group. After the phototherapy effect, the total protein activation analysis was performed, in which no differences were observed for any of the groups studied. In this way the Laser phototherapy, LED and Magneto application, the partial modulation of the osteoblasts was observed in relation to the viability, But in the process of differentiation of alkaline phos- phase activity there were few alterations.